The Effect Of Work Motivation, Quality Of Work Life, And Job Satisfaction On Teacher Performance - Pratama, Burhana Rizky; Wahidmurni, Wahidmurni; Harini, Sri (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
The position of the teacher is very strategic and decisive in the teaching and learning process because the task of the teacher is to sort and select the learning material to be presented to students. One of the important factors to achieve optimal teacher performance by providing good work motivation, a conducive work environment supports work activities. Job satisfaction with the job will contribute greatly to improving teacher performance. The purpose of the study is to (1) Analyze and explain the effect of work motivation on performance in teachers, (2) Analyze and explain the effect of quality of work life on performance in teachers, (3) Analyze and explain the effect of job satisfaction on performance in teachers of State High School 2 Batu City. The research method uses correlative with a quantitative approach. Questionnaire data collection using questionnaires. The population is 67 teachers. Data analysis using logistic regression. The results showed that partial work motivation had a significant positive effect on performance; Quality of work life has a significant positive effect on performance; Job satisfaction has a significant positive effect on performance. Work motivation, quality of work life, and job satisfaction has a significant positive effect simultaneously on the performance of teachers of State High School 2 Batu City.Kedudukan guru sangat strategis dan sangat menentukan dalam proses belajar mengajar karena tugas guru yang memilah dan memilih bahan pelajaran yang akan disajikan kepada peserta didik. Salah satu faktor yang penting untuk mencapai kinerja guru yang optimal dengan memberikan motivasi kerja yang baik, lingkungan kerja yang kondusif mendukung aktivitas kerja. Kepuasan kerja dengan pekerjaannya akan memberikan kontibusi besar terhadap peningkatan kinerja guru. Tujuan dari penelitian untuk (1) Menganalisis dan menjelaskan pengaruh motivasi kerja terhadap kinerja pada guru, (2) Menganalisis dan menjelaskan pengaruh quality of worklife terhadap kinerja pada guru, (3) Menganalisis dan menjelaskan pengaruh kepuasan kerja terhadap kinerja pada guru SMA Negeri 2 Kota Batu. Metode penelitian menggunakan korelatif dengan pendekatan kuantitatif. Pengumpulan data angket menggunakan kuesioner. Populasi sebesar 67 guru. Analisis data menggunakan regresi logistik. Hasil penelitian menunjukkan secara parsial motivasi kerja berpengaruh positif signifikan terhadap kinerja; Quality of work life berpengaruh positif signifikan terhadap kinerja; Kepuasan kerja berpengaruh positif signifikan terhadap kinerja. Motivasi kerja, quality of work life, dan kepuasan kerja berpengaruh secara positif signifikan secara simultan terhadap kinerja guru SMAN 2 Kota Batu.